Drains influence on the beach groundwater hydrodynamics - Fischione, Piera; Celli, Daniele; Pasquali, Davide; Di Risio, Marcello (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value="{"1":2,"2":"The aim of this paper is to investigate the role in the groundwater level dynamics played by drains of a Beach Drainage System (BDS) with different nominal diameters.Three different cases are considered: drained beach without incoming waves; undrained beach with incoming waves, and drained beach with incoming waves. Hence, a preliminary numerical investigation on the hydrodynamics inside a sandy beach is carried out, accounting for the presence of both short water waves and a BDS. The (Volume Averaged) Reynolds Averaged Navier Stokes (RANS) equations are solved by using the Finite Volume Method, and the\rVolume of Fluid (VOF) is used to track the groundwater table fluctuations by using an OpenFoam® solver. To represent the draining surface, the atmospheric pressure at the drain boundary is imposed. In order to reproduce the concentrated head losses, a low permeability layer around the drain is used. The model is able to catch the damped behaviour of the water table oscillation inside the sandy porous medium forced by the incoming short waves. In case of drained beaches, the drain dimensions play an important role in the outflow velocities at the boundary of the pipe. On the other hand, the drain diameter does not affect the\rgeneral behaviour of the groundwater level inside the beach, but within an area close to the drain location."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The aim of this paper is to investigate the role in the groundwater level dynamics played by drains of a Beach Drainage System (BDS) with different nominal diameters.Three different cases are considered: drained beach without incoming waves; undrained beach with incoming waves, and drained beach with incoming waves. Hence, a preliminary numerical investigation on the hydrodynamics inside a sandy beach is carried out, accounting for the presence of both short water waves and a BDS. The (Volume Averaged) Reynolds Averaged Navier Stokes (RANS) equations are solved by using the Finite Volume Method, and the Volume of Fluid (VOF) is used to track the groundwater table fluctuations by using an OpenFoam® solver. To represent the draining surface, the atmospheric pressure at the drain boundary is imposed. In order to reproduce the concentrated head losses, a low permeability layer around the drain is used. The model is able to catch the damped behaviour of the water table oscillation inside the sandy porous medium forced by the incoming short waves. In case of drained beaches, the drain dimensions play an important role in the outflow velocities at the boundary of the pipe. On the other hand, the drain diameter does not affect the general behaviour of the groundwater level inside the beach, but within an area close to the drain location.